Justifying the structure of the improved mechanism for manual control of motor vehicles’ pedals - Vitaliy Korendiy; Nazarii Fedunyshyn; Vasyl Kozub (Transport Technologies)
Due to the challenging military situation in Ukraine, the demand for tailored and flexible pedal control systems for individuals with physical disabilities is especially important. Standard pedal configurations often fail to meet the specific needs of drivers with limited mobility, making vehicle operation both difficult and potentially unsafe. The development of specialized manual control devices, such as hand-operated pedals or adjustable foot controls, is crucial for ensuring that these drivers can manage their vehicles with accuracy and safety. Such innovations not only improve accessibility but also foster greater autonomy and inclusion, empowering disabled drivers to navigate the roads with confidence and ease.